A System Engineering Approach to Sustainability Decision Support System Based on SDGs - Syaukani, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a Sustainability Decision Support System (SDSS) based on the Sustainable Development Goals (SDGs) using a System Engineering approach at the Institut Teknolgi Bisnis dan Bahasa 'Dian Cipta Cendikia' (ITBA DCC). The main issues faced are a lack of a structured system to integrate environmental, social, economic, and governance aspects into policy campus. The methodology study covers six phases: Main, which includes Requirements Analysis, System Design, Implementation, Testing, Deployment, and Maintenance. This system merges Multi-Criteria Decision Making (MCDM) techniques, modeling system dynamics, and data analytics to visualize SDGs progress, prioritize programs, and provide recommendation strategies. Research results show that SDSS is capable of increasing transparency, accountability, and effectiveness in data-driven decision-making. The novelty of the study lies in its multidisciplinary and contextual approach to college-level vocational education in Indonesia. This system also has the potential to be replicated in other institutions as an innovative model for management sustainability